Changes in the nutrient composition of top-selling packaged foods and beverages in Colombia between 2016 to 2021 - Forero, Luis Carlos; Gómez, Luis F.; Mora-Plazas, Mercedes; Parra-Murillo, María; Toquica, Sara; Taillie, Lindsey Smith (Frontiers in Nutrition, 2025)
IntroductionIn 2022, the Colombian government approved a law requiring by 2024 the use of Front of Package octagonal warning labels in food products with an excess of nutrients of concern for chronic disease, including sodium, sugar, saturated fat, and trans-fat, as well as non-nutritive sweeteners (NNS). In addition, the government began 2023 by applying a 10% tax on sugar-sweetened beverages and foods that also had warning labels for sodium, sugar and saturated fat. This tax increased to 15% in 2024 and to $20% in 2025. While a previous study examined the changes in the nutritional composition of beverage and food products offered in Colombia between 2016 and 2018, it is necessary to update this information to understand whether the industry anticipated labeling and tax regulations by reformulating products.MethodsThis study carried out a comparison of the content of selected nutrients of concern and non-nutritive sweeteners (NNS) from the nutritional panels of 164 matched pairs of packaged foods and beverages from the top selling brands in Colombia in 2021 compared to 2016. McNemar’s test for paired data was used to evaluate changes in the proportion of each of the critical nutrients and NNS to be regulated.ResultsThere were no significant changes in sodium, saturated fat, trans fat, or free sugar in foods or beverages prior to policy implementation. However, there was a significant increase in the presence of NNS in beverages, during this pre-policy period from 32 to 59%.ConclusionThese findings suggest that changes in nutrient composition of packaged foods and beverages had been marginal before the implementation of the tax and warning labeling laws.